Transformation of natural ecosystems affected by climate change in the Khanty-Mansi Autonomous Okrug – Yugra, Russia - O.N. Lipka; S.V. Krylenko; A.P. Andreeva; A.Yu. Bogdanovich; A.S. Karavaeva (Transformat︠s︡ii︠a︡ ėkosistem, 2025)
The article presents the analysis of both observed (1960–present) and modeled (present–2100) changes in climate parameters, and their observed and probable consequences for ecosystems, including transformation. In 1960–2021, the average annual air temperature in the Khanty-Mansi Autonomous Okrug Yugra (KhMAO) was increasing as 0.33–0.52 °C/10 years, the annual amount of precipitation, as 3–15 mm/10 years. The number of dangerous hydrometeorological phenomena associated with abnormally low temperatures has decreased, while those associated with abnormally high temperatures, intense precipitation and droughts, have increased. The intensity of 19 dangerous hydrometeorological phenomena in the area is sufficient to cause significant damage to natural systems, including irreversible changes. The floods, wildfires, and droughts are the most dangerous. Changes in the timing of phenological events and shifts in the species ranges, including the emergence of invasive species, have been recorded. The results of bioclimatic modeling confirm that in the second half of the XXI century, the current boundaries of biomes will not correspond to the climatic conditions on most of the studied territory. The natural conditions of the northern taiga will be replaced by those observed for the middle taiga; in the southern areas, preconditions for steppe formation may emerge. Such climate change is favorable for 112 rare species with northern border of ranges located in KhMAO, but they are unfavorable for 20 arctic species. The potential change of biomes in the region to become of the southern (warmer) type will be accompanied by an increase in biological diversity and productivity of ecosystems.